Clinical Profile and Complications Experienced by Chronic Kidney Disease Patients undergoing Hemodialysis in a Tertiary Hospital of Nepal: An Observational Study - Bimala Sah; Imran Khan; Ashesh Dhungana (Journal of Nepal Medical Association)
Introduction: Chronic kidney disease is emerging public health problems globally. Hemodialysis is the commonest treatment modality but it causes some complications and fluctuation in parameters. This study aimed to assess the clinical profile and complications experienced by chronic kidney disease patients undergoing hemodialysis.